PENINGKATAN KETERAMPILAN MENULIS NARASI SISWA DENGAN MENGGUNAKAN MEDIA GAMBAR BERSERI KELAS IV SD NEGERI BONTORAMBA 1 KOTA MAKASSAR - nafila; Selvi, Nurhayati; Erniati, Erniati (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
This study aims to find out: How to improve students' narrative writing skills using serial picture media for class IV SD Negeri Bontoramba 1 Makassar City. This type of research uses classroom action research (CAR). The research subjects were fourth grade students at SD Negeri Bontoramba 1 Makassar. Data collection techniques are observation, tests and documentation. The data in this study were analyzed using descriptive quantitative statistical analysis. The results of the research carried out showed that the improvement in students' narrative writing skills using serial picture media increased as seen from teacher and student observations as well as test results where cycle I showed that the percentage of students whose scores were above the KKM only reached 30% so that the student scores above the KKM increased to 85%. Based on the results of the research and discussion, it can be concluded that using serial image media can improve students' narrative writing skills. at SD Negeri Bontoramba 1 Makassar.